Novel Small Molecule Inhibitors Targeting the IL-6/STAT3 Pathway or IL-1β - Jihye Yoo (Molecules, 2022)
Development of small molecules that inhibit inflammatory cytokines is a desirable strategy for the treatment of inflammatory diseases such as rheumatoid arthritis (RA). Following up a previous study, we synthesized 10 novel compounds with a 2,5-diaminobenzoxazole moiety and evaluated their biological activities. Among them, compound 3e showed potent inhibitory activity on Interleukin 6 (IL-6)/Signal Transducer and Activator of Transcription 3 (STAT3) signaling inhibition (71.5%), and 3a showed excellent inhibitory activity on Interleukin 1 (IL-1β) (92.1%). To test in vivo anti-inflammatory activity, compounds 3a and 3e were administered by intraperitoneal (IP) injection after subcutaneous (SC) injection of zymosan A into the right footpad of mice. Inflammation on the footpad was reduced after administration of compounds 3a and 3e. Especially, compound 3a showed a significant ameliorative effect on zymosan-induced inflammation. From the in vivo and in vitro test results, we confirmed that our synthesized compounds are effective on the RA animal model through inhibition of the IL-6/STAT3 signaling pathway. Since drugs developed with small molecule inhibitors have several advantages over biological drugs, further study on these compounds is needed for the development of potent SMI drugs on RA.